The effect of occupational safety and health on employee productivity in furniture industry - Etruly, Niki; Nafi'ah, Roikhanatun (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2023)
The risk of work accidents is a major concern in companies.Â This is caused by the consequences that occur in work accidents to the deadly consequences of these accidents, so risk analysis even more important. The business process of the furniture industry from upstream to downstream has risk of occupational accidents. This study aims to determine the effect of occupational safety and health on employee productivity. Based on the results of data analysis, it can be concluded that the occupational safety does not have a significant effect on work productivity and occupational health variableÂ has a significant effect on work productivity. Simultaneously the independent variables have a significant relationship with work productivity. For future research, other variables that influence productivity can be added, such as leadership style, work discipline, and work motivation to expand the research area, so that it can produce new thoughts or studies.